Mathematical model of fish-productivity estimation in the Northern Caspian on the annual primary production of phytoplankton - A. F. Sokol'skii; G. M. Abdurahmanov; E. A. Sokol'skaya (Юг России: экология, развитие, 2015)
In the work there is presented mathematic model of counting the fish catching by measuring the seasonal primary production of phytoplankton of the Northern Caspian. The model has shown its representativeness and is offered to use to specialists.